Multimodal Anaesthesia in a Crab-eating Fox (Cerdocyon thous) Undergoing Hemilaminectomy and Sacrococcygeal Stabilization - De Azevedo, Milena Castro; Moraes, Vinicius de Jesus; Schaffer, Débora Passos Hinojosa; Dórea Neto, Francisco de Assis; Iwassa, Carlos Hiroshi Duarte; Barbosa, Vivian Fernanda (Acta Scientiae Veterinariae, 2020)
Background: Several researches have shown the impacts of roads more directly to wildlife in Brazil. The crab-eating fox (Cerdocyon thous) is a frequent run over victim. Dissociative drugs are commonly used, but inhalation anesthesia is indicated in cases of extensive and prolonged surgeries. Despite their similarity with domestic dogs, the literature is scarce regarding the association of new anesthetic techniques and protocols in wild canids. The aim of this paper was to report the viability of multimodal anesthesia in a crab-eating fox, victim of running over, undergoing hemilaminectomy and sacrococcygeal stabilization. Case: An adult male specimen of crab-eating fox was rescued after being run over and taken to a wild animal screening center. Physical examination showed superficial and deep pain, lack of support for the pelvic limbs and proprioception, increased reflexes, and reduced tail mobility. Chemical restraint with intramuscular (IM) tiletamine-zolazepam (6.0 mg/kg) and morphine (0.5 mg/kg) was performed. Meloxicam (0.2 mg/kg IM) and enrofloxacin (5.0 mg/kg IM) were also administered. The animal was sequentially admitted to the veterinary hospital. Radiographic images showed compaction of the spinal column of the T10 and T11 thoracic vertebrae and the sacrococcygeal region. Sixty min after chemical restraint, the anesthesia was supplemented with IM tiletamine-zolazepam (4.5 mg/kg), and fluid therapy with 0.9% NaCl (10 mL/kg/h) was started. Ten min later, intravenous propofol dose-effect (2.5 mg/kg) was administered and general anesthesia was maintained with isoflurane (FiO2 = 1.0). Thirty min after the induction of anesthesia, the animal was urdergoing hemilaminectomy and sacrococcygeal stabilization. Constant rate infusions (CRI) of dexmedetomidine (0.5 μg/kg/h) and ketamine (0.6 mg/kg/h) were started. Lidocaine (7.0 mg/kg) and bupivacaine (2.0 mg/kg) were administered into the surgical site on the T10 and T11 vertebrae at 35 and 80 min into the surgery, respectively. The isoflurane requirement was adjusted often to keep the animal in the surgical anesthetic plan. At the end of the surgery (total time, 95 min), lumbosacral epidural analgesia was performed with morphine (0.1 mg/kg). No important abnormalities were detected in heart rate, systolic arterial pressure, mean arterial pressure, diastolic arterial pressure, respiratory rate, oxygen saturation, or body temperature during the surgical period. The time intervals between the end of anesthesia, and the following events: extubation, the first head movement, and the establishment of sternal were 18, 34 and 73 min, respectively. Recovery was considered calm and peaceful, with no signs of pain or excitement. Discussion: Considering the painful discomfort and the need for manipulation, dissociative anesthesia was initially used to move the animal to hospital care. Due to the immediate indication for surgery, it was decided to use propofol in a sufficient dose for orotracheal intubation, keeping anesthesia with isoflurane. With the expectation of severe pain during the surgical procedure, CRI of dexmedetomidine and ketamine were used, in addition to lidocaine and bupivacaine at the lesion site. Although the minimum alveolar concentration of isoflurane has not been recorded, the physiological parameters were kept relatively stable, ratifying the adequate plan of anesthesia compatible with the observed eye reflexes. Based on the experience with other canids, the use of epidural morphine was performed, aiming at postsurgical analgesic extension. Although a certain lack of coordination was observed, the animal’s recovery was characterized by stillness, with no signs of pain or excitement, confirming the effectiveness of the anesthetic protocol. The present report may aid in the choice of balanced anesthetic approaches in wild canids.